2017
DOI: 10.1074/jbc.m117.791400
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine dictates the assembly and dynamics of caveolae in the plasma membrane

Abstract: Edited by Dennis R. VoelkerCaveolae are bulb-shaped nanodomains of the plasma membrane that are enriched in cholesterol and sphingolipids. They have many physiological functions, including endocytic transport, mechanosensing, and regulation of membrane and lipid transport. Caveola formation relies on integral membrane proteins termed caveolins (Cavs) and the cavin family of peripheral proteins. Both protein families bind anionic phospholipids, but the precise roles of these lipids are unknown. Here, we studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 63 publications
6
56
0
Order By: Relevance
“…High PS concentration is a hallmark of the cytosolic leaflet of the PM and is important for diverse cellular processes, from establishment of cell polarity, signaling and cytoskeleton organization to control of endocytosis and caveolae formation (Fairn et al, 2011;Sun and Drubin, 2013;Takano et al, 2008;Hirama et al, 2017). Identification of proteins that specifically transport PS to the PM in yeast and in mammalian cells represented an important step towards understanding how this PS enrichment is achieved (Maeda et al, 2013;Chung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…High PS concentration is a hallmark of the cytosolic leaflet of the PM and is important for diverse cellular processes, from establishment of cell polarity, signaling and cytoskeleton organization to control of endocytosis and caveolae formation (Fairn et al, 2011;Sun and Drubin, 2013;Takano et al, 2008;Hirama et al, 2017). Identification of proteins that specifically transport PS to the PM in yeast and in mammalian cells represented an important step towards understanding how this PS enrichment is achieved (Maeda et al, 2013;Chung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the PtdSer-binding specificity via the cavin UC1 domain that is required for caveola stability and the role of PtdSer in caveola formation 35 , we next analysed whether PtdSer levels determined CAV1/cavin1 association. PSA3 cells generate less endogenous PtdSer when grown in medium containing dialyzed fetal bovine serum (DFBS), but PtdSer can be restored to near control levels by 10 µM ethanolamine (Etn) supplementation [16][17][18][19][20]36 .…”
Section: Association Of Caveolin and Cavin1 Requires Distinct Ptdser mentioning
confidence: 99%
“…PC is also a prominent phospholipid in caveolae (Huot et al, 2010;Pike et al, 2005;Smart et al, 1999), while PS has been found to be abundant in the cytoplasmic leaflet of caveolae (Fairn et al, 2011;Pike et al, 2005). The depletion of PS was shown to result in the loss of caveolar morphology (Hirama et al, 2017). The main fatty acids of caveolar phospholipids are oleic acid (C18:1), palmitic acid (C16:0) (Cai et al, 2013;Huot et al, 2010), and stearic acid (C18:0) (Cai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%